2020
DOI: 10.1136/annrheumdis-2020-218484
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lockdown on rheumatology outpatient care in the age of COVID-19

Abstract: Clinic General rheumatology clinic Systemic lupus erythematosus clinic Period Prelockdown During lockdown Prelockdown During lockdown Total scheduled patients (%) 1126 328 704 289 Total attended (%) 988 (87.7) 240 (73.2) 639 (90.8) 223 (77.2) New cases 27 9 9 2 Repeated cases 961 231 630 221 Defaulted (%) 138 (12.3) 88 (26.8) 65 (9.2) 66 (22.8)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The study confirmed the findings of the WHO in a substantial number of Mexican outpatients with chronic rheumatic diseases. We found that one in two patients experienced HCI, in line with results of previous reports from the United States [ 19 , 25 ] and Europe [ 3 , 26 ], although higher percentages had been described among surveyed patients attending rheumatology services in 35 European countries [ 27 ], and attending a general rheumatology clinic at designated COVID-19 hybrid hospital in Malaysia [ 28 ]. The reasons for medical care interruption highlight a combination of institutional decisions to temporally close outpatient clinics and patients’ own decisions to avoid hospital visits [ 19 , 25 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study confirmed the findings of the WHO in a substantial number of Mexican outpatients with chronic rheumatic diseases. We found that one in two patients experienced HCI, in line with results of previous reports from the United States [ 19 , 25 ] and Europe [ 3 , 26 ], although higher percentages had been described among surveyed patients attending rheumatology services in 35 European countries [ 27 ], and attending a general rheumatology clinic at designated COVID-19 hybrid hospital in Malaysia [ 28 ]. The reasons for medical care interruption highlight a combination of institutional decisions to temporally close outpatient clinics and patients’ own decisions to avoid hospital visits [ 19 , 25 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…(Long) disease duration, substantial disease activity level previous HCI, need for rheumatic care, and NP with (rheumatic disease-related) treatment were associated with clinical deterioration. Hassen et al [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] surveyed 3000 rheumatic patients during the current pandemic in Saudi Arabia, with the aim to capture patients' experiences. Among the 637 respondents, patient perception of worsened disease activity was correlated to unplanned healthcare visits (which might be considered a surrogate for the need for rheumatic medical care), medication non-adherence (a surrogate for NP with treatment), and difficulty in accessing medication, which was in fact the main reason for treatment discontinuation among our patients.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Data from the United States show a 60% decline in in-person outpatient visits from mid-February to late March 2020. 15 In Malaysia, Singh et al 16 demonstrated a reduction of 70.9% in general rheumatology clinics and 58.9% in SLE clinics. In a rheumatology center in Mexico, 51.3% of patients did not receive any kind of specialty care at the beginning of the pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…[8][9][10][11] The new Coronavirus Disease 2019 (COVID-19) unprecedentedly evolved and challenged health care systems with a specific impact on patients with long-term conditions. 12 Rheumatoid arthritis patients were affected by the partial or total closure of outpatient clinics that was applied during the pandemic and negatively affected disease management 13 and aggravated the RA-related psychological burden, paralleled with the pandemic-associated psychological impact due to social distancing and the fear of contracting the disease. 14 In addition, the governmental authorities and the Centers for Disease Control and Prevention (CDC) have also highlighted that COVID-19 implies a threat to patients with long-term and autoimmune disorders.…”
Section: Introductionmentioning
confidence: 99%